“Multiphonic Virtuoso” for Alto Saxophone A Creative Research in Music Composition - Pruksavanich, Wisuwat (Rangsit Music Journal, 2025)
This creative research explores the application of contemporary saxophone techniques, with a particular focus on Multiphonic, in the composition Multiphonic Virtuoso for Alto Saxophone. Contemporary techniques encompass sounds and methods distinct from traditional playing styles and are increasingly prominent in modern music. Since the invention of the saxophone in 1842, compositions for the instrument have evolved rapidly, with composers incorporating innovative techniques to expand its expressive range. These advancements have led to the creation of unique sounds and textures, broadening the scope of saxophone music and its place in various musical genres. The significance of these techniques is particularly evident in the works presented at the 18th Thailand International Composition Festival, which highlight their potential in redefining saxophone repertoire. This study investigates the potential and challenges of Multiphonic while examining their integration into the progressive rock genre. The composition itself demands a high level of technical skill from performers, who must navigate intricate rhythms, challenging fingerings, and the distinctive tonal qualities of multiphonic. The research process is structured into three main stages. First, a theoretical exploration of Multiphonic was conducted using textbooks and compositions as primary sources. This stage aimed to provide a solid foundation in understanding the mechanics and applications of Multiphonic. Second, experimentation and refinement of fingerings specific to the alto saxophone were undertaken. This phase was crucial in adapting the technique for practical use on the instrument. Finally, the third stage focused on the composition and performance of Multiphonic Virtuoso, synthesizing theoretical knowledge and practical experimentation into a cohesive artistic output. Key references in the study include Les Sons Multiples Aux Saxophones by Daniel Kientzy and Hello! Mr. Sax by Jean-Marie Londeix. These seminal works provide detailed fingering charts and comprehensive insights into the execution of Multiphonic, serving as invaluable resources for this research. Additionally, the study analyzed compositions by contemporary composers such as Christian Lauba, François Rossé, and Barry Cockcroft, who have innovatively incorporated Multiphonic into their works. These analyses highlighted the creative potential of the technique and its diverse applications in modern saxophone repertoire. Through rigorous experimentation, the researcher developed specialized fingerings tailored to the alto saxophone. These fingerings address critical performance challenges, including pitch accuracy, tonal stability, and ergonomic finger placement, ensuring that the technique is both effective and practical for performers. The composition Multiphonic Virtuoso for Alto Saxophone represents the culmination of this research. Initially composed for tenor saxophone in 2023, the piece was subsequently adapted for alto saxophone in 2024. This adaptation was prompted by practical considerations and feedback from musicians, who highlighted the alto saxophone’s suitability for the composition’s technical demands. The transition from tenor to alto saxophone required significant adjustments, as the two instruments differ in fingering systems and tonal characteristics. This process involved further experimentation to refine the fingerings and adapt the technical aspects of the composition to the new instrument. In Multiphonic Virtuoso, Multiphonic serve as the central element, shaping the piece’s sonic identity. The composition integrates Multiphonic with other instruments, including electric guitar, electric bass, synthesizer, and drum kit, creating a dynamic fusion of contemporary saxophone techniques and progressive rock. This blending of elements expands the expressive possibilities of the saxophone while introducing new dimensions to the genre. Key compositional techniques employed in the piece include substituting traditional melodies with Multiphonic to create unconventional tonal palettes, using complex rhythmic structures to enhance timbral depth, and thoroughly testing fingerings to ensure the piece’s playability. The result is a composition that not only showcases the technical and expressive potential of Multiphonic but also pushes the boundaries of saxophone music within a progressive rock context. The research findings underscore the transformative potential of Multiphonic in saxophone performance and composition. By incorporating these techniques, saxophonists can achieve a broader range of tonal and textural possibilities, enriching the instrument’s repertoire. Moreover, the study demonstrates how Multiphonic can bridge the gap between contemporary classical music and other genres, such as progressive rock, fostering a dialogue between diverse musical traditions. Despite the challenges associated with mastering Multiphonic—including precise embouchure control, optimal airflow management, and adapting to unconventional fingerings—the research provides valuable insights and solutions to these issues. For instance, the specialized fingerings developed during the study offer practical strategies for overcoming technical hurdles, enabling performers to execute Multiphonic with understanding and accuracy. In conclusion, this research has produced a distinctive composition that exemplifies the creative and technical possibilities of contemporary saxophone techniques. Multiphonic Virtuoso not only highlights the potential of Multiphonic as a central element in saxophone music but also offers a new perspective on their application in a progressive rock setting. The study’s findings contribute to the broader discourse on contemporary saxophone performance, providing a framework for further exploration of advanced techniques. By addressing the challenges of Multiphonic and presenting innovative solutions, this research paves the way for future developments in saxophone music and its integration into diverse musical genres.